Walking Unsettling Depremacy: A Preliminary Proposition for Questioning the Right to Go Anywhere. (February 2022) - Decter, Leah
As an expression of the "right to go anywhere, " walking or hiking in settler states, particularly on recreational infrastructures such as the Trans Canada Trail, can be understood to support a form of white settler emplacement that is contingent on Indigenous dis placement. These infrastructures and activities also contribute to assumptions of settler-state sovereignty over Indigenous lands common to the contemporary settler colonial project. In this article, I consider these conditions alongside arts-based methodologies I have developed from a critical white settler perspective to reveal, challenge, and subvert them. A discussion of my video, l i s t e n, demonstrates how one such methodology, unsettling depremacy, critically contends with specific interactions with place. I conclude by proposing walking unsettling depremacy as methodology in development that can be deployed to interfere with the ways white settler walking and its recreational infrastructures assert colonial claim.